2017
DOI: 10.17116/jnevro20171176199-105
|View full text |Cite
|
Sign up to set email alerts
|

Low back pain and Modic changes

Abstract: Modic changes (MCh) are pathological changes in the bone marrow and the endplates of adjacent vertebrae characterized by bone marrow edema, fatty degeneration or osteosclerosis that are revealed by high-power field magnetic resonance imaging (MRI). The dominant disease pattern is a persistent back pain syndrome with varying intensity. It leads to difficulties in the interpretation of clinical data, evaluation of MRI data and treatment. The article presents a modern conception of the pathogenesis, classificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 56 publications
1
1
0
Order By: Relevance
“…A Russian study published in 2017 summarized the pathogenesis and other aspects of the relationship of Modic changes with chronic low back pain. 17 Our results also concluded that Modic changes were commonly seen in patients with low back pain. Type II Modic changes were most frequently seen in these patients.…”
Section: Discussionsupporting
confidence: 71%
“…A Russian study published in 2017 summarized the pathogenesis and other aspects of the relationship of Modic changes with chronic low back pain. 17 Our results also concluded that Modic changes were commonly seen in patients with low back pain. Type II Modic changes were most frequently seen in these patients.…”
Section: Discussionsupporting
confidence: 71%
“…Moreover, in 2015, Hayashi et al [ 9 ] believed that age, disc degeneration, angular motion, and translational motion were significantly linked to MCs in the lumbar spine, and the translational motion of lumbar segments increased with type II MCs, whereas angular motion decreased as the type of MCs increased. Therefore, a number of scholars [ 10 – 12 ] believe that MCs are closely related to LBP, vertebral body motion, and spine degeneration.…”
Section: Introductionmentioning
confidence: 99%